Comparative Analysis of Financial Performance: Conventional Banks vs. Sharia Banks - Fischer Mirakhor Bashir; Cohen Gorton (Indonesia Accounting Research Journal, 2023)
His research compares the financial performance of conventional and Sharia banks to identify operational trends and their ramifications. The study examines financial data, risk management, customer behavior, and market perception in these two banking systems. Conventional banks perform well due to their wide product offerings and market presence. Due to their interest-based income, they have greater ROA and ROE. These banks are vulnerable to interest rate changes and market uncertainty, requiring diligent risk management. Sharia banks emphasize ethics, social responsibility, and risk-sharing. Due to interest-based income and interest rate risk management limits, they struggle to achieve profitability while attracting a specific customer base. Comparative analysis yields strategic recommendations for both institutions. To improve financial performance and address shortcomings, revenue diversification, ethical compliance, risk management, regulatory adaptation, innovation, customer-centricity, and strategic communication are essential. The banking industry must balance financial innovation with ethical compliance, according to this report. This method ensures client value and need responsiveness in a changing financial context. Banks may navigate a competitive marketplace and meet diverse client financial needs by following these concepts. This analysis helps create a banking environment that is inclusive, responsive, and matched with varied client groups' changing requirements and beliefs.